Spatio-temporal variability in the Cladocera assemblage of a subtropical hypersaline lagoon - Rosa,J. C. L. (2022)
Abstract Cladocera represent an important zooplankton group because of their seasonal prominence in terms of abundance and their contribution in controlling primary production (phytoplankton). On a global scale, there are few studies on Cladocera in hypersaline environments. The present work aims to evaluate the spatio-temporal variation of the Cladocera assemblage across a salinity gradient in the habitats of the Araruama Lagoon. Samples were collected in random months over a period of four years at 12 fixed stations in the Araruama Lagoon using a WP2 plankton net equipped with a flow meter. Our results do not reveal significant influence of the tide and seasonal variation as factors affecting the Cladocera assemblage. Five Cladocera species were found in the Araruama Lagoon, only in stations 11 and 12 where they reached an average of 1,799 ± 3,103 ind. m-3. The mean of the Shannon Diversity Index was 0.45 ± 0.2. The species that stood out in terms of frequency and abundance were: Penilia avirostris (frequency of occurrence: 71%), followed by Pseudevadne tergestina (41%). The same species also stood out in terms of relative abundance, Penilia avirostris (87%) and Pseudevadne tergestina (11%). The absence of Cladocera in the innermost parts of the lagoon suggests that their entrance to these locations is possibly inhibited by the salinity and temperature gradient of the lagoon, being the main factors influencing the dynamics of the Cladocera assemblages.